Медико-соціальна характеристика первинної інвалідності внаслідок цукрового діабету в осіб молодого віку - Вернигородська, М. В.; Вернигородський, В. С.; Забур’янова, В. Ю. (Clinical Endocrinology and Endocrine Surgery, 2013)
The results of data analysis of primary disability due to diabetes mellitus in the population of working age in the dynamics for 5 years at the Vinnitsa region (n = 1034) with a detailed feature a contingent of young disabled people – 281 people presented in this article. The increase in the proportion of young people with disabilities, especially up to 30 years (2.1 times) with type 1 diabetes among newly registered disabled due to diabetes mellitus and stable increase in the level of the primary disability in young adults in the last 3 years was established. In the structure of disability the prevalence of disabled group III predominantly male was revealed.